Development And Performance Analysis Of Alumina-Yttria Stabilized Zirconia-Chromia Cutting Tool For High Wear Performance - Tamin, Norfauzi (2020)
Alumina based cutting tool have gradually garnered huge applications in refractory process especially in machining industries. This is due to their excellent hot hardness and abrasion resistance that could shear the work piece material efficiently especially in dry condition. However, their inherent properties such as brittleness, low thermal shock resistance and sensitive to the cutting load have led to difficulty in providing longer tool life which limit their applications. This study presents the improvement of alumina (A1203) based cutting tool by addition of zirconia (Zr02) and chromia (Cn03) content. The development of these cutting tools were divided into four parts. The first part focused to determine the effective processing parameters with variations of polyethylene glycol (PEG) content (0.6-1.25 wt. 0/0) as binder, sintering temperature (12000C-14000C) and cold isostatic pressing (CIP) pressure (200-400 MPa). The second part focused on the formulation of A1203, Zr02 and Cr203 compositions to produce effective cutting tool based on the hardness, density, flexural strength and coefficient of friction (COF). Various content of Zr02 (0, 5, 10, 15, 20 and 25 wt.%) and Cn03 (0, 0.2, 0.4, 0.6 and 0.8 wt.%) were added into dominant A1203 powders and consistently processed by using parameters determined from the first part of study. The third part focused on the comparison of machining performance for the fabricated cutting tools based on the tool life and wear mechanism. The fourth part focused on the optimization of machining parameters based on the response surface methodology (RSM) and analysis of variance (ANOVA). The results from the first part highlighted that the effective content of PEG binder recorded at 0.6 wt%. The samples recorded maximum hardness and density at 62.5 HRc and 3.692 g/cm3 when CIP pressure was set at 300 and 60-second dwell time and the sintering temperature was set at 14000C and 9 hours soaking time. For the second part of the study, A1203-Zr02 with ratio 80-20 wt% produced hardness, relative density and bending strength of 70.07 PRC, 97% and 1449.33 MPa respectively. This value was changed to 71.03 HRc, 95.8% and 856.02 MPa when 0.6 wt% Cr203 were added into the 80-20 wt% A1203-Zr02. A1203-Zr02 mixed Cr203 presented lower COF (0.23) as compared to A1203 Zr02 (0.28) and A1203 (0.34). At the third part of the study, cutting tool fabricated from A1203-Zr02 mixed Cr203 with ratio 80-20-0.6 wt.% recorded highest tool life of 360-second with 33.33% improvement of tool life as compared to 80-20 wt.% ZTA (240-second) and 75% improvement of pure A1203 (90-second). The optimization of cutting parameters on the final part of the study proposed that the cutting speed of 200 m/min, feed rate of 0.125 mm/rev and depth of cut 0.50 mm obtained 99% desirability to produce minimum wear rate. Overall, the addition of 0.6 wt.% Cr203 into A1203-Zr02 matrix adequately enough to evaporate and reacted with the A1203 to generate anisotropy-oriented particles at the upper surface of the product. Such structure enabled stronger particle compact formed due to the interlocking grains at the affected area.